High zinc wheat for sub-Saharan Africa - Guwela, Veronica Faith (2023)
Zinc deficiency affects over 17% of the global population. Risk deficiencies of up to 96% have been reported in Sub Saharan Africa, mostly due to increased poverty levels and high dependence on cereal diets with low bioavailable zinc. In Africa, although wheat provides up to 20% of dietary energy, cultivated wheat is inherently low in essential micronutrients such as grain zinc (Zn) and iron (Fe), and the genetic variability is relatively narrow. Genetic biofortification of food crops is considered a sustainable and cost-effective approach for alleviating mineral nutrient deficiencies. Wheat progenitors and wild relatives are considered as potential sources of genetic variation for crop improvement. Inductively coupled plasma mass spectrometry (ICP-MS) was undertaken to determine the natural variation in grain Zn and selected essential mineral nutrients (Fe, Ca and Se) of wheat wild relative accessions, in order to identify novel sources of genetic variation. Accessions from the genus Triticum, Aegilops, Thinoprum, Amblyopyrum and Secale were screened. Results showed a wide variation in grain Zn, Fe, Ca and not Se. Triticum urartu and Amblyopyrum muticum accessions showed the highest grain Zn and Fe, whilst Thinopyrum species showed the highest Ca concentration. A preliminary study of 48 pre-breeding introgression lines (doubled haploids) derived from T. urartu and Am. muticum also showed a wide variation in grain Zn, Fe, Ca and not much in Se.